The apocalypse - Jones, Justin; Latt, David Michael; de los Rios, Carlos ([Distributed by] Echo Bridge Home Entertainment ; distributed in the Philippines by Viva Video, 2010)
In this epic film of faith, a mother and father search for their only child as a giant asteroid headed for Earth triggers a series of apocalyptic events.